The Phenomenon of Youtuber as a Jobs in The Modern Era (Case Study of Meranti Village Youtuber) - Yuanda, Boby Harum; T. Ilham Saladin (Talenta Publisher, 2023)
In today's modern era, researchers want to see how the emergence of a new job into people's lives, especially the people of Meranti Village, researchers want to see how the phenomenon of YouTubers in Meranti Village can become a job in the modern era?, and the purpose of this study is to find out how the YouTube application can be more used in the realm of new work in today's modern era. This type of research is qualitative research, the subject of this research is Meranti Village YouTubers, namely Beny, Mugi, Febi, Oddy, Deny, Agus, Arief and Koko Data collection techniques in this study are by using observation, interviews, documentation, and conclusions. Informant determination using purposive sampling. The results showed that the phenomenon of YouTubers as a job in the modern era that occurred in Meranti Village was due to an era progress that continued to grow and to the efficiency of the work done by them and could get a fairly decent income and easy to do the work, researchers also saw how they did their daily lives from waking up in the morning, starting to create content until night editing videos. Researchers also see how YouTubers can change social and economic status, but there are also some YouTubers who fail and don't continue it.